2020
DOI: 10.1109/tbme.2020.2967079
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Nonlinear Interaction in the Nervous System Based on Phase-Locked Amplitude Relationship

Abstract: This paper introduces the Crossfrequency Amplitude Transfer Function (CATF), a model-free method for quantifying nonlinear stimulus-response interaction based on phase-locked amplitude relationship. Method: The CATF estimates the amplitude transfer from input frequencies at stimulation signal to their harmonics/intermodulation at the response signal. We first verified the performance of CATF in simulation tests with systems containing a static nonlinear function and a linear dynamic, i.e., Hammerstein and Wien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This nonlinear, U-shaped relationship in which COT decreases then increases as a variable continually increases in value has been observed with walking speed 1 , 2 , stride frequency 3 , 5 , and TA muscle activity 42 . Prior studies have shown that muscle proprioceptive feedback is best modeled as a non-linear system 21 , 43 45 . So even as the amount of energy absorbed through muscle fascicle stretch may continually increase with walking speed, its relationship does not necessarily need to be linear to be useful to the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…This nonlinear, U-shaped relationship in which COT decreases then increases as a variable continually increases in value has been observed with walking speed 1 , 2 , stride frequency 3 , 5 , and TA muscle activity 42 . Prior studies have shown that muscle proprioceptive feedback is best modeled as a non-linear system 21 , 43 45 . So even as the amount of energy absorbed through muscle fascicle stretch may continually increase with walking speed, its relationship does not necessarily need to be linear to be useful to the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies used sum-of-sinusoid stimulations to the wrist joint and found not only harmonics and subharmonics but also intermodulation patterns [6,29]. The majority of intermodulation responses presented the second-order nonlinearity, which is the sum or the difference between input frequencies [8]. These findings indicate that the nonlinearities in the somatosensory system allow the functional integration of input signals at different frequencies, and they can be transmitted in different somatosensory ascending pathways.…”
Section: A Nonlinear Cortical Response To Somatosensory Inputsmentioning
confidence: 97%
“…This effect typically occurs in a mono-synaptic neural system such as the corticospinal tract where the supraspinal motor command is linearly transferred to the motor output due to the pool effect of motor units [4]. However, multi-synaptic neural systems, such as the somatosensory system, have been reported highly nonlinear, showing harmonic responses to periodic stimuli [5][6][7][8]. Cross-frequency coupling in the corticothalamic interactions has also been reported when characterising essential tremor [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies used sum-of-sinusoid stimulations to the wrist joint and found not only harmonics and subharmonics but also intermodulation patterns [6, 29]. The majority of intermodulation responses presented the second-order nonlinearity, which is the sum or the difference between input frequencies [8]. These findings indicate that the nonlinearities in the somatosensory system allow the functional integration of input signals at different frequencies, and they can be transmitted in different somatosensory ascending pathways.…”
Section: Neurological and Clinical Applicationsmentioning
confidence: 99%
“…This effect typically occurs in a mono-synaptic neural system such as the corticospinal tract where the supraspinal motor command is linearly transferred to the motor output due to the pool effect of motor units [4]. However, multi-synaptic neural systems, such as the somatosensory system, have been reported highly nonlinear, showing harmonic responses to periodic stimuli [5][6][7][8]. Cross-frequency coupling in the corticothalamic interactions has also been reported when characterising essential tremor [9].…”
Section: Introductionmentioning
confidence: 99%